School Culture Management at Private Madrasah Ibtidaiyah Plumpung Magetan - Nisak, Hernik Khoirun (Jurnal Paradigma, 2024)
School culture has a very important role in improving school quality and making schools effective. The importance of school culture is because school culture is an identity for school personnel, so it is easy to recognize and differentiates one school from another. The aim of this research is to describe and analyze; School culture profile, Implementation of school culture, Efforts to develop and maintain school culture at the PlumpungMagetan Private Madrasah Ibtidaiyah. The data sources in this research are the Principal, Teachers and parents of students. The research method used is a qualitative method through a case study design. Data collection was carried out through a process of interviews, observation and documentation studies. Data validity is carried out through a process of credibility, transferability, dependability and confirmability